2022
DOI: 10.3389/fnsyn.2022.911020
|View full text |Cite
|
Sign up to set email alerts
|

The Yin and Yang of GABAergic and Glutamatergic Synaptic Plasticity: Opposites in Balance by Crosstalking Mechanisms

Abstract: Synaptic plasticity is a critical process that regulates neuronal activity by allowing neurons to adjust their synaptic strength in response to changes in activity. Despite the high proximity of excitatory glutamatergic and inhibitory GABAergic postsynaptic zones and their functional integration within dendritic regions, concurrent plasticity has historically been underassessed. Growing evidence for pathological disruptions in the excitation and inhibition (E/I) balance in neurological and neurodevelopmental d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 210 publications
(192 reference statements)
0
17
0
Order By: Relevance
“…Glutamate and GABA are the main neurotransmitters regulating excitation and inhibition in the human brain [ 59 ], as also evinced by human imaging studies [ 60 ]. Stress exposure has been suggested to impair neuronal integrity of excitatory glutamate neurons and inhibitory GABA interneurons in limbic and cortical brain areas also implicated in major affective disorders [ 61 ].…”
Section: Animal Models Of Social Isolation Distressmentioning
confidence: 99%
“…Glutamate and GABA are the main neurotransmitters regulating excitation and inhibition in the human brain [ 59 ], as also evinced by human imaging studies [ 60 ]. Stress exposure has been suggested to impair neuronal integrity of excitatory glutamate neurons and inhibitory GABA interneurons in limbic and cortical brain areas also implicated in major affective disorders [ 61 ].…”
Section: Animal Models Of Social Isolation Distressmentioning
confidence: 99%
“…Recent studies, using genetically targeted recordings, enabled an insight into the mechanisms whereby distinct interneurons participate in the formation of hippocampal memory 5,6 . This expanding knowledge on GABAergic inhibition encouraged a more "holistic" approach considering additionally plasticity at GABAergic synapses and its interplay with the glutamatergic drive [8][9][10][11] . Consequently, in the past decade or so, GABAergic inhibition was shown to undergo many forms of plasticity and the underlying molecular mechanisms start to be unraveled 8 .…”
mentioning
confidence: 99%
“…This expanding knowledge on GABAergic inhibition encouraged a more "holistic" approach considering additionally plasticity at GABAergic synapses and its interplay with the glutamatergic drive [8][9][10][11] . Consequently, in the past decade or so, GABAergic inhibition was shown to undergo many forms of plasticity and the underlying molecular mechanisms start to be unraveled 8 . In particular, we have recently shown that stimulation of transmembrane adhesion molecules, integrins with specific peptides induced different types of GABAergic plasticity in the hippocampus 12 while Kawaguchi and Hirano (2006) reported that α3β1 integrin suppressed long-term potentiation at inhibitory synapses on the cerebellar Purkinje neurons.…”
mentioning
confidence: 99%
“…To this end, significant diversity in excitatory and inhibitory neurons in the cerebral cortex revealed by single-cell sequencing will be discussed. Glutamatergic neurons, as the most common and widely studied excitatory neurons in cortical circuits, have important molecular signatures and specific physiological properties ( Birey et al, 2017 ; Chapman et al, 2022 ; Zhong et al, 2022 ). This importance also holds true for GABAergic neurons in inhibitory circuits and long-range projections ( Rock et al, 2017 ; Kirmse and Zhang, 2022 ).…”
Section: Advances In Studying Cortical Neurons and Circuits ...mentioning
confidence: 99%